Percutaneous endoscopic gastrostomy in neurologic patient population: Indications, coplications and outcome - Mehmet ARSLAN; Serap ARSLAN; Yusuf BAYRAKTAR; Halis ŞİMŞEK and Gürol ÖKSÜZOĞLU and Abdurrahman Kadayıfçı and Ali Rıza SOYLU and Burhan KAYHAN (Turkish Journal of Gastroenterology, 2019)
-